PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI DAN SELF ESTEEM PADA SENJANGAN ANGGARAN DENGAN PEMODERASI KOHESIVITAS KELOMPOK DI BANK PERKREDITAN RAKYAT SE-BALI - Gine Das Prena; A.A Kt Alit Supryadinata (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
A budget is an organized plan and is expressed in a monetary unit for a company's operations and resources for a certain period in the future. Budgetary slack as a budgeting process that is found to be intentional distortion by reducing budgeted income and increasing budgeted costs, in words another budgetary slack is the diference prediction between the stated budget and the best budget estimate that can honestly predict. This study to analyst the empirical evidence from influence of group cohesiveness in moderating the effect of budgetary participation, information asymmetry, and self esteem on budgetary slack. In this study, the location of the research conducted was the Rural Credit Bank (BPR) in the Province of Bali with a total sample of 57 respondents from Rural Credit Bank (BPR) in the Province of Bali. The sample in this study used the purposive sampling method. Data analysis techniques used are Moderated Regression Analysis (MRA).The results showed that group cohesiveness strengthened the influence of budgetary participation on budgetary slack, group cohesiveness weakened the influence of information asymmetry on budgetary slack, group cohesiveness strengthened the effect of self esteem on budgetary slack.